IMPLEMENTASI KEBIJAKAN KEPROTOKOLAN DALAM PENINGKATAN PELAYANAN PIMPINAN DAERAH KABUPATEN BOLAANG MONGONDOW UTARA - SUKRI MAUDA; Arifin Tahir; Karlina Napu (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The research objectives are: 1) to find out more about how to implement protocol policies; 2) to find out what factors can influence the implementation of protocol policies; 3) the results of this study are expected to be useful and beneficial for government employees, especially employees in the Protocol and Communication Section of the Regional Secretariat of the North BolaangMongondow Regency; 4) this research is also expected to increase knowledge to be able to improve services to regional leaders; 5) as a reference and also a reference/sources for further researchers in research related to the implementation of protocol policies. This study uses a descriptive qualitative research type, with an inductive approach where this research describes systematically and accurately about specific facts and then draws a generalization that has a general nature from a series of efforts to answer various questions regarding problems in policy protocols in an effort to improve services to leaders. area in an argumentative manner from the results of the researcher's thinking. The results of this study are indicate that: there are 4 factors that influence the implementation of protocol policies in improving the service of regional leaders in North BolaangMongondow Regency, namely: 1) communication; 2) resources; 3) disposition; 4) bureaucratic structure.